Etos Kerja Kepala Sekolah di SMA Quran Darul Fattah Kecamatan Rajabasa Kota Bandar Lampung - Agung Prayitno; Cipto Handoko; Muhammad Yasin (Sekolah Tinggi Ilmu Syrari’ah Daru ‘Ulum (STSDU) Lampung Timur., 2023)
When doing a job, a person's style and motivation will show whether he works seriously or just pretends to. If you are responsible or not, etc. The views, expectations, and habits of the work group shape how a person lives and does their job. So, a person's work ethic can be changed by the work ethic of the group. The goal of this study was to find out how hard the principal of the Quran Darul Fattah High School in Bandar Lampung City's Rajabasa District works. This type of research is called